Notes on an idiophone used in Kabile initiation rites by the Mbae - Carrington, John F. (International Library of African Music, 1954)
In October, 1953, I sent to the British Museum parts of a tripartite musical apparatus used by the Mbae (Bamanga) tribe during the initiation rites known as Kabile. These were obtained shortly before I left for furlough in Europe in 1950 and I hoped on my return a year later to visit the Mbae area and obtain records of the music used for dancing in which this apparatus played a part. In 1951, however, I had to take up work in another part of Congo and have not yet been able to visit the Mbae country. It may be worth while writing a short note on the interesting idiophone seen, for comparison with similar instruments used elsewhere in the hope that a fuller account, accompanied by musical data, may be published later.
Keywords: Musical instruments; Ethnomusicology; Initiation rites; Mbae (African people); Music; Dance; Idiophones; Belgian Congo; African Music